Governmentality and counter-hegemony in Bangladesh - Alam, S. M. Shamsul (© 2015 S. M. Shamsul Alam, 2016)
This book was published in Springer [© 2015 S. M. Shamsul Alam ] and the definite version is available at: http://www.springer.com/gp/book/9781137537140 The article website is at: http://link.springer.com/book/10.1007%2F978-1-137-52603-8